Sleep disturbances in Malaysian children with cerebral palsy - Atmawidjaja, Raymond Warouw; Wong, Sau Wei; Yang, Wai Wai; Ong, Lai Choo (Wiley-Blackwell Publishing, 2014)
Aim The aim of the study was to compare the frequency and type of sleep disturbances in a group of Malaysian children aged 4 to 18 years with cerebral palsy (CP) with their nearest-age, able-bodied siblings and to identify factors associated with sleep disturbances. Method The study was a case–control study of 109 children with CP (61 males, 48 females; mean age 9y, SD 3y 11mo, range 4–18y) and their healthy siblings (56 males, 53 females; mean age 10y, SD 3y 9mo, range 4–18y). The Sleep Disturbances Scale for Children (SDSC) questionnaire was completed by the main caregiver. In children with CP, multiple regression analysis was be used to determine factors related to higher Total SDSC sleep scores. Results Ninety-seven children (89%) had spastic CP, 10 (9%) had dyskinetic CP, and two (2%) had mixed CP. Based on the Gross Motor Function Classification System (GMFSC), 34 patients (31%) were at GMFSC level I or II, 10 patients (9%) at level III, and 65 patients (60%) at level IV or V. Children with CP scored significantly higher than their siblings on Total SDSC and four SDSC subscale scores – difficulty in initiating and maintaining sleep, sleep breathing disorders, sleep–wake transition disorders, and sleep hyperhidrosis. Caregiver sleep duration of less than 7 hours (p=0.02) and caregiver sleep latency of more than 30 minutes (p=0.03) were significantly associated with higher Total SDSC scores. Co-sleeping was not a significant factor. Interpretation Sleep disturbances are more common in children with CP than in their siblings. Attention should be given to caregiver sleep when evaluating sleep disturbances in children with CP as this factor was shown to be associated with higher Total SDSC scores.